Penggunaan Media Flash Card untuk Meningkatkan Motivasi dan Hasil Belajar IPS - Rismawati Rismawati; Salamah Salamah (Proceedings Series on Social Sciences & Humanities, 2022)
The success of learning can be measured from the learning outcomes obtained by students. High learning outcomes can be seen from the achievement of minimum criteria competencies that are exceeded by students. Students tend not to have the motivation to learn with a monotonous learning design. Innovative learning design will be able to increase student motivation and learning outcomes This research was aimed to know that using of audio visual media could increase motivation and learning outcome of social studies in elementary school. Method which used in this research was PTK it was consist of three cycles, each cycles has planning, implementation, observation and reflection. Result of this research showed that there was an increasing on: (1) student’s motivation to learn, which 60,25% on 1st cycle, 75,19% on 2nd , and 91 % on 3rd cycle; (2) student’s learning outcomes in cognitive aspect increased from average value 71,53 on 1st cycle, 73,71 on 2nd cycle, 80,66 on 3rd cycle, in affective aspect was 66,25% on 1st cycle,75,19% on 2nd cycle, 92% on 3rd cycle, in psychomotor aspect increased from average value 71,08 % on 1st cycle, 75,18 % on 2nd cycle, and 80,59 on 3rd cycle. Implication, based on research was flash card media could increase learning motivation and the increasing of learning motivation could increase learning outcome.